Mid-infrared materials and devices on a Si platform for optical sensing - Vivek Singh; et al. (Science and Technology of Advanced Materials, 2014)
In this article, we review our recent work on mid-infrared (mid-IR) photonic materials and devices fabricated on silicon for on-chip sensing applications. Pedestal waveguides based on silicon are demonstrated as broadband mid-IR sensors. Our low-loss mid-IR directional couplers demonstrated in SiNx waveguides are useful in differential sensing applications. Photonic crystal cavities and microdisk resonators based on chalcogenide glasses for high sensitivity are also demonstrated as effective mid-IR sensors. Polymer-based functionalization layers, to enhance the sensitivity and selectivity of our sensor devices, are also presented. We discuss the design of mid-IR chalcogenide waveguides integrated with polycrystalline PbTe detectors on a monolithic silicon platform for optical sensing, wherein the use of a low-index spacer layer enables the evanescent coupling of mid-IR light from the waveguides to the detector. Finally, we show the successful fabrication processing of our first prototype mid-IR waveguide-integrated detectors.